Engineering a protease-based and site-specific PEGylation-based strategy for the controlled release of exenatide. Issue 42 (30th June 2020) - Zhang, Aihong; Lin, Yin; Nong, Shirly; Zhao, Wei; Dong, Mei
Abstract : Using the commercially available antidiabetic drug exenatide (exendin-4) as a model peptide, we designed a novel exenatide derivative, termed LEX-1, comprising a 12-mer albumin-binding peptide, a protease-sensitive linker and a native exenatide. Abstract : Using the commercially available antidiabetic drug exenatide (exendin-4) as a model peptide, we designed a novel exenatide derivative, termed LEX-1, comprising a 12-mer albumin-binding peptide, a protease-sensitive linker and a native exenatide. In addition, site-specific PEGylation was performed using LEX-1 as a lead sequence to generate four exenatide derivatives (LEX-2 to LEX-5). Moreover, we determined the optimal molecular weight of maleimide-derivatized PEG for the site-specific PEGylation of LEX-1 by an in vitro stability assay and an in vivo hypoglycemic efficacy test. As a result, LEX-3 (PEG10 kDa) exerted enhanced proteolytic stability, rational release rate of free exenatide and the best glucose-stabilizing capability compared with others. In addition, the prolonged hypoglycemic effects of LEX-1 and LEX-3 were demonstrated in type 2 diabetic mice by multiple OGTTs and a hypoglycemic duration test. Furthermore, a pharmacokinetic test was conducted using Sprague Dawley (SD) rats; LEX-3 (PEG10 kDa) showed the best circulating t 1/2 of ∼119.7 h for exenatide release from LEX-3, suggesting that LEX-3 has the potential to be developed into a once-weekly antidiabetic agent. The consecutive 8 week treatment of both LEX-1 and LEX-3 exhibited enhanced beneficial efficacies on body weight gain, cumulative food intake, % fat and hemoglobin A1c (HbA1c) reduction compared with exenatide treatment. Meanwhile, the chronic administration of LEX-1 and LEX-3 also effectively improved the blood biochemical indexes. Our results indicate the enhanced antidiabetic effects of LEX-1 and LEX-3, and our strategy of PEGylation and albumin conjugation can be applied to other bioactive agents.